2023
DOI: 10.1002/advs.202205044
|View full text |Cite
|
Sign up to set email alerts
|

Nanomodified Switch Induced Precise and Moderate Activation of CAR‐T Cells for Solid Tumors

Abstract: Chimeric antigen receptor (CAR)-T cell therapy is a transformative treatment against advanced malignancies. Unfortunately, once administrated in vivo, CAR-T cells become out of artificial control, and fierce response to CAR-T therapy may cause severe adverse events, represented by cytokine-release syndrome and on-target/off-tumor effects. Here, a nanomodified switch strategy is developed, leading to sustained and precise "on-tumor only" activation of CAR-T cells. Here, original gelatinase-responsive nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(34 reference statements)
0
2
0
Order By: Relevance
“… 22 In Wang's research, gelatinase‐responsive NPs were used to create a “NanoSwitch” that can activate CAR‐T cells at the tumor site, addressing safety issues with CAR‐T therapy regardless of the target. 23 In this study, a “universal” TCR‐T‐cell therapy was developed by modifying tumor cell antigens externally. The universal TCR‐T therapy can enable tumor cells to be identified and killed by TCR‐T cells regardless of antigen expression, tumor HLA typing, or TCR‐T type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 In Wang's research, gelatinase‐responsive NPs were used to create a “NanoSwitch” that can activate CAR‐T cells at the tumor site, addressing safety issues with CAR‐T therapy regardless of the target. 23 In this study, a “universal” TCR‐T‐cell therapy was developed by modifying tumor cell antigens externally. The universal TCR‐T therapy can enable tumor cells to be identified and killed by TCR‐T cells regardless of antigen expression, tumor HLA typing, or TCR‐T type.…”
Section: Discussionmentioning
confidence: 99%
“…Sun and his team were the first to develop a universal CAR‐T‐cell therapy that targets antigens, using a nanosystem that fuses with cells 22 . In Wang's research, gelatinase‐responsive NPs were used to create a “NanoSwitch” that can activate CAR‐T cells at the tumor site, addressing safety issues with CAR‐T therapy regardless of the target 23 . In this study, a “universal” TCR‐T‐cell therapy was developed by modifying tumor cell antigens externally.…”
Section: Discussionmentioning
confidence: 99%
“…Reproduced with permission. 125 Copyright 2023, John Wiley and Sons. (B) The F-AgNP modified exogenous antigens onto the tumor cell membranes, which provided sufficient targets for CAR-T cell recognition, enabling CAR-T cell to exert antitumor effects independent of tumor inherent antigen profiles.…”
Section: Improvement Of the Safety Of Car-t Therapymentioning
confidence: 99%
“…6A). 125 Sun et al found that it is possible to load exogenous antigens onto nanoparticles (F-AgNPs). The F-AgNPs modify exogenous antigens to tumor cell membranes via membrane fusion.…”
Section: Improvement Of the Safety Of Car-t Therapymentioning
confidence: 99%